Test - retest reliability and validity of the Prakriti assessment questionnaire in patients with gynecological diseases - Karunagoda, K.P.K.R.; Perera, P.K.; Senanayake, H. (University of Colombo, 2019)
This study was designed to validate a Prakriti assessment questionnaire through the scientific method. Prakriti is one of a basic concepts discussed in Ayurveda which can categorise population into several subgroups, based on phenotypic characters like appearance, temperament and habits. Traditionally, Prakriti assessment is done by an Ayurveda physician with clinical investigations but in resent times several tools have been developed to assess the Prakriti, including questionnaires. In this study cases were selected randomly from the outpatient department of the Gynecology unit, National Ayurveda Hospital, Borella. Cross cultural adaptation was achieved by translating the questionnaire from the original version, performed by independent mother tongue translator with an Ayurveda background, followed by committee review. Test-retest reliability was examined for 40 subjects who completed the tool twice within a 14 day interval. Cronbach's Alpha was run to test the test-retest reliability of the questioner. Reliability for the Prakriti assessment questionnaire from the 1s administration to the 2nd attempt was 0.585 to 0. 453 respectively. This study noted less than optimal reliability for the Sinhala version of the Prakriti assessment questionnaire. Despite this finding, modifications of the tool are still necessitated by the absence of gold standard Prakriti assessment measurement for the Sinhala speaking population. Therefore, it is necessary to develop a more sophisticated tool which can be used for research and clinically in Ayurveda medicine in Sri Lanka.
Keywords: Prakriti; Prakriti assessment questioner; test re test reliability